Membaca Tantangan Krisis Keesaan - Huliselan, Beril (Theologia in Loco, 2023)
This article attempts to review and analyze the challenges posed by the ecumenical crisis, both at the global level and in Indonesia. Several documents are used to analyze the extent to which the studies of ecumenical crisis have taken place, and then to see the similarities with the ecumenical crisis in Indonesia. The documents-based data are processed using qualitative software to see what the existing problems and the patterns are; related to the connection between the data. This article also focuses on analyzing the 2021-2023 PGI program, which distinguishes it from other articles that analyze the ecumenical crisis in a more general way, without going into analyzing the ecumenical council-related program.